A material for treating fluoride in sewage and its application
By using calcium-modified aluminum-lanthanum mixed metal oxide materials, the problems of low adsorption efficiency and small capacity of existing adsorption materials have been solved, achieving efficient and economical wastewater fluoride treatment, and the materials are recyclable.
Patent Information
- Application Number
- CN202411162044.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Existing adsorption materials have low adsorption efficiency and small adsorption capacity for fluoride, resulting in low wastewater treatment efficiency and high cost, and making it difficult to continuously recycle them.
Calcium-modified aluminum-lanthanum mixed metal oxides were used as adsorbents. A porous carbon material with high specific surface area was formed by reacting a biological template with soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt in urea solution. Combined with the strong affinity of calcium for fluoride, efficient adsorption of fluoride ions was achieved.
It improves adsorption capacity and efficiency, reduces treatment costs, and extends the material's service life through an alkaline regeneration process, achieving efficient and economical wastewater fluoride treatment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a material for treating fluoride in sewage and its application. Background Art
[0002] Fluoride is considered to be one of the important trace elements in our daily drinking water. The appropriate fluoride content in drinking water plays an important role in the healthy growth of the human body. Intake of low concentrations of fluoride ions contributes to the development of tooth enamel and normal mineralization of bones. However, intake of high concentrations of fluoride ions can lead to fluorosis, bone deformities and soft tissue metabolism problems. In the drinking water standard recommended by the World Health Organization (WHO), the concentration of fluoride is not more than 1.5 mg / L. my country stipulates in the "Sanitary Standard for Drinking Water" (GB 5749-2022): The limit value of fluoride in drinking water is 1.0 mg / L. When small-scale centralized water supply and decentralized water supply are limited by water sources and water purification technology, the fluoride index shall be implemented at 1.2 mg / L. The causes of fluoride pollution include both geological structural factors, such as regional high-fluoride groundwater, and modern industries such as aluminum, chemical, glass, metal, fertilizer, semiconductor and battery manufacturing industries. The discharge of fluoride-containing industrial wastewater.
[0003] Many methods have been developed to remove fluoride from aqueous solutions, including precipitation, coagulation, ion exchange, membrane separation, electrochemical treatment and adsorption. Among them, the adsorption method has the advantages of simple operation, recyclability and high removal rate, so it has been widely studied. The adsorption method uses adsorbent materials for treatment. The adsorbent material has a large specific surface area, which can adsorb fluoride compounds in wastewater and has a good defluorination effect; however, the existing adsorbent materials have certain defects when used, such as the low adsorption efficiency of fluorine by the adsorbent material, which leads to low wastewater treatment efficiency; in addition, the adsorption capacity of the existing adsorbent material is relatively small, and a large amount of defluoridation agent often needs to be added during each adsorption process, resulting in high sewage treatment costs, large defluorination sludge output, and inconvenient operation and management.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a material and application for treating fluoride in sewage; the material for treating fluoride in sewage achieves efficient adsorption and defluorination, increases adsorption capacity, and greatly improves the comprehensive effect of sewage treatment.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A material for treating fluoride in sewage, wherein the material for treating fluoride in sewage is a calcium-modified aluminum-lanthanum mixed metal oxide, and the raw materials thereof include a biological template, a soluble lanthanum salt, a soluble aluminum salt, a soluble calcium salt and urea; the biological template includes one or more combinations of cotton cellulose, cattail fluff and cotton wool;
[0008] The method for preparing the material for treating fluoride in sewage comprises the following steps:
[0009] S1, washing the bio-template with alcohol, taking it out and drying it, then soaking it in a hydrochloric acid solution, filtering and washing it until the pH of the filtrate is 6.9-7.1, and drying it to obtain a pretreated bio-template; alcohol washing is to remove surface impurities and organic pollutants to ensure the purity and active surface of the template;
[0010] S2, mixing and dissolving the pretreated bio-template, soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt in water to obtain a first mixed solution; the weight ratio of the bio-template, lanthanum ions, aluminum ions, and calcium ions is 10:3:(1.4-2.8):4; the soluble lanthanum salt is one of lanthanum nitrate, lanthanum chloride, and lanthanum acetate; the soluble aluminum salt is one of aluminum chloride, aluminum sulfate, and aluminum nitrate; the soluble calcium salt is one of calcium chloride, calcium sulfate, and calcium nitrate;
[0011] S3, adding urea to the first mixed solution and stirring to obtain a second mixed solution, adding the second mixed solution to a reactor and heating to obtain a hydroxide precipitate;
[0012] S4, washing the obtained hydroxide precipitate with deionized water and anhydrous ethanol for more than 3 times, and then drying at 70-90° C. for more than 11 hours to obtain a powder;
[0013] S5. calcining the obtained powder at a temperature of 600-700° C. for 3-5 hours to obtain calcium-modified aluminum-lanthanum mixed metal oxide, which is a material for treating fluoride in sewage.
[0014] Furthermore, the bio-template is flocculent or velvety; these bio-templates have rich pore structures and can provide good template effects; after calcination, the bio-template forms a stable carbon skeleton while retaining the original shape and structure during the calcination process, generating hollow carbon tubes or porous carbon materials. These carbon-based materials have high surface area, good conductivity and chemical stability; at the same time, they also have good adsorption properties. The present invention uses aluminum and lanthanum elements as basic components, which not only provide the necessary stability and mechanical strength, but also the Lewis acid sites of aluminum oxide and the special electronic structure of lanthanide oxides can work together to create favorable conditions for the adsorption of fluoride ions. Calcium is evenly dispersed in the mixed metal oxide. As a strong fluorine-loving element, calcium can effectively attract and fix fluoride ions in the environment, and reduce the fluorine content through chemical reactions or physical adsorption mechanisms.
[0015] Further, in step S1, the organic solvent used for alcohol washing is isopropanol or 25% ethanol;
[0016] In step S2, the biological template, soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt are ultrasonically dissolved in water for 15 to 25 minutes at an ultrasonic frequency of 20 to 50 kHz; the first mixed solution is mixed by magnetic stirring at a magnetic stirring speed of 500 to 100 rpm for a mixing time of 10 to 20 minutes;
[0017] In step S3, in the second mixed solution, the molar concentration of urea is 8-12 mmol / L, and the heating temperature of the second mixed solution is 160-200° C.; urea can also be replaced by ammonia or sodium bicarbonate.
[0018] The present invention also proposes an application of the aforementioned material for treating fluoride in sewage, specifically for removing fluoride ions from fluoride-containing sewage; based on the volume of the fluoride-containing sewage, the dosage of the material for treating fluoride in sewage is 1 to 1.5 g / L.
[0019] Furthermore, for sewage with a fluoride content of ≤5 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment material in the sewage is not less than 3 minutes;
[0020] For sewage with a fluoride content greater than 5 mg / L and not more than 20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment materials in the sewage shall not be less than 15 minutes;
[0021] For sewage with a fluoride content ≥ 20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment materials in the sewage shall not be less than 2 hours.
[0022] Furthermore, the material for treating fluoride in sewage is regenerated every 5 to 7 days, or when the adsorption efficiency of the material drops to about 80% of the original efficiency. The regeneration method is as follows: the fluoride-containing sewage to which calcium-modified aluminum-lanthanum mixed metal oxide is added is subjected to solid-liquid separation, the solid is soaked in a 0.4 to 0.6 mol / L sodium hydroxide solution for 22 to 26 hours, and then centrifuged and dried to obtain the regenerated material for treating fluoride in sewage.
[0023] The beneficial effects of the present invention are:
[0024] (1) The present invention utilizes the porous structure and high surface area provided by the biological template to promote the co-precipitation of lanthanum, aluminum, and calcium ions with the biological template to form a uniform hydroxide precipitate under the alkaline environment generated by the thermal decomposition of urea, and then converts the precipitate into a stable calcium-modified aluminum-lanthanum mixed metal oxide through high-temperature calcination; the material has a high specific surface area and good adsorption performance, which solves the problem of low adsorption capacity of raw materials, provides abundant adsorption sites for fluoride ions, has a large adsorption capacity, and can effectively remove fluoride in sewage.
[0025] (2) The material for treating fluoride in sewage synthesized by the present invention is rich in Lewis acid sites and calcium ions, has a very high affinity for fluoride ions, and can effectively adsorb fluoride in water. In addition, the active sites of the rare earth lanthanum ions designed in the material are fully exposed, further enhancing the selective recognition and efficient capture of fluoride.
[0026] (3) After use, the fluoride treatment materials in sewage can be effectively restored to their adsorption properties through a simple alkaline solution soaking process; this is because the alkaline solution can neutralize and release the adsorbed fluoride ions; followed by centrifugal separation and drying, the materials can be quickly restored to their original state and put into use again; the regeneration of fluoride treatment materials in sewage not only significantly extends the service life of the materials and reduces the long-term treatment costs, but also overcomes the limitation of conventional materials that are difficult to recycle continuously, providing new technical support for sustainable water resource management. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0028] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0029] A material for treating fluoride in sewage, wherein the material for treating fluoride in sewage is a calcium-modified aluminum-lanthanum mixed metal oxide, and the raw materials thereof include a biological template, a soluble lanthanum salt, a soluble aluminum salt, a soluble calcium salt and urea; the biological template includes one or more combinations of cotton cellulose, cattail fluff and cotton wool;
[0030] The method for preparing the material for treating fluoride in sewage comprises the following steps:
[0031] S1. Wash the bio-template in isopropanol or 25% ethanol, remove and dry, then soak in a hydrochloric acid solution, filter and wash until the pH of the filtrate is 6.9-7.1, and dry to obtain a pretreated bio-template;
[0032] S2, dissolving the pretreated bio-template, soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt in water by ultrasonication for 15 to 25 minutes, and magnetically stirring for 10 to 20 minutes (magnetic stirring speed is 500 to 100 rpm) to obtain a first mixed solution; mixing the pretreated bio-template with the soluble lanthanum salt, aluminum salt, and calcium salt in water, and using ultrasonication to assist in dissolving the metal ions (La 3+ 、Al 3+ , Ca 2+ ) are evenly dispersed in the solution; this process ensures that the metal ions can be evenly deposited in the pore structure of the bio-template, providing a uniform source of metal ions for the subsequent co-precipitation reaction;
[0033] The weight ratio of the biological template, lanthanum ions, aluminum ions, and calcium ions is 10:3:(1.4-2.8):4; for example, taking cotton cellulose, lanthanum nitrate, aluminum nitrate, and calcium nitrate as an example, the weight ratio is 1:1(2-4):2;
[0034] S3, adding 8-12 mmol / L urea to the first mixed solution and stirring to obtain a second mixed solution, adding the second mixed solution to a reactor and heating it to 160-200° C. to precipitate oxides;
[0035] Urea decomposes to generate ammonia (NH3) and carbon dioxide (CO2) during heating. Ammonia dissolves in water to generate ammonium hydroxide (NH4OH), increasing the alkaline environment of the solution. The alkaline environment promotes the reaction between metal ions and hydroxide ions to generate corresponding hydroxide precipitates (La(OH)3, Al(OH)3, Ca(OH)2). The hydroxides are uniformly deposited with the assistance of the pretreated biological template to form a precipitate in the secondary mixed solution.
[0036] S4, washing the obtained hydroxide precipitate with deionized water and anhydrous ethanol for more than 3 times, and drying at 70-90° C. for more than 11 hours to obtain a powder;
[0037] S5, calcining the obtained powder at 600-700° C. for 3-5 hours to obtain calcium-modified aluminum-lanthanum mixed metal oxide, which is a material for treating fluoride in sewage;
[0038] The dried powder is calcined at high temperature to remove residual organic matter and volatiles, and at the same time convert the hydroxide into the corresponding oxides (La2O3, Al2O3, CaO); the calcination process also promotes the interaction and compounding between the oxides to form calcium-modified aluminum-lanthanum mixed metal oxides; this process significantly improves the crystallinity, chemical stability and adsorption properties of the material, solving the problem of low adsorption capacity of raw materials.
[0039] Furthermore, the bio-template is flocculent or velvety. These types of bio-templates have rich pore structures, can provide good template effects, and are inexpensive. The bio-template is washed in 25% anhydrous ethanol or isopropanol to remove surface impurities and organic pollutants, ensure the purity and active surface of the template; then soaked in a hydrochloric acid solution to further clean the surface of the bio-template, while introducing acidic functional groups to increase the active sites on the surface of the bio-template. Finally, the bio-template is repeatedly filtered and washed to neutrality, and a pretreated bio-template is obtained after drying; the pretreated bio-template provides a clean, highly active surface for subsequent reactions.
[0040] Specifically, the fiber length of cotton cellulose is generally 0.5 to 3 cm, so as to be evenly dispersed and form a stable carbon skeleton, and the moisture content is controlled below 5%. The length of cattail fluff is generally 0.5 to 2 cm, maintaining appropriate fluffiness, and the moisture content is controlled below 10%. Cotton wool has a good floc structure, the fiber length is generally 1 to 5 cm, and the moisture content is controlled below 8%.
[0041] Further, in step S2, the soluble lanthanum salt is one or more of lanthanum nitrate, lanthanum chloride, and lanthanum acetate; the soluble aluminum salt is one of aluminum chloride, aluminum sulfate, and aluminum nitrate; the soluble calcium salt is one of calcium chloride, calcium sulfate, and calcium nitrate; the present invention selects aluminum and lanthanum elements as basic components, which can not only provide the necessary stability and mechanical strength, but also the Lewis acid sites of aluminum oxide and the special electronic structure of lanthanide oxide can work together to create favorable conditions for the adsorption of fluoride ions. Calcium is evenly dispersed in the mixed metal oxide. As a strong fluorine-loving element, calcium can effectively attract and fix fluoride ions in the environment, and reduce the fluorine content through chemical reaction or physical adsorption mechanism. The specially treated bio-template forms a stable carbon skeleton during the calcination process, generating hollow carbon tubes or porous carbon materials, while retaining the shape and structure of the original template, which can guide the formation of a porous, high specific surface area three-dimensional sponge-like structure during the material synthesis stage, and has good conductivity and chemical stability; this structure not only greatly increases the internal surface area of the material, providing abundant adsorption sites for fluoride ions, but also promotes the rapid transmission and effective capture of fluoride ions within the material, ensuring the efficient defluorination process. The bio-template may produce microporous and mesoporous structures during the calcination process. These pore structures give the carbon material a high specific surface area and good adsorption properties, allowing the calcined bio-template to be used as an adsorbent to remove fluoride and improve purification efficiency.
[0042] The present invention also proposes an application of the aforementioned material for treating fluoride in sewage, specifically for removing fluoride ions from fluoride-containing sewage; based on the volume of the fluoride-containing sewage, the dosage of the material for treating fluoride in sewage is 1 to 1.5 g / L.
[0043] Furthermore, for sewage with a fluoride content of ≤5 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment material in the sewage is not less than 3 minutes; for sewage with a fluoride content greater than 5 mg / L and not more than 20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment material in the sewage is not less than 15 minutes; for sewage with a fluoride content of ≥20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment material in the sewage is not less than 2 hours; for sewage with different fluoride contents, the present invention can achieve better treatment effects in a relatively short time.
[0044] Furthermore, the material for treating fluoride in sewage is regenerated every 5 to 7 days, or when the material adsorption efficiency drops to about 80% of the original efficiency. The regeneration method is as follows: solid-liquid separation is performed on the fluoride-containing sewage added with calcium-modified aluminum-lanthanum mixed metal oxide, and the solid is soaked in 0.4 to 0.6 mol / L sodium hydroxide solution for 22 to 26 hours, and then centrifuged and dried to obtain the regenerated material for treating fluoride in sewage; the alkali solution can neutralize and release the adsorbed fluoride ions, and then the material is quickly returned to its original state through centrifugal separation and drying, so that it can be put into use again. This not only significantly extends the service life of the material and reduces the long-term treatment cost, but also overcomes the limitation that conventional materials are difficult to recycle continuously, providing new technical support for sustainable water resource management.
[0045] The following is a specific description of the treatment effects using a plurality of embodiments, comparative examples and three verification examples of different fluorine content.
[0046] The reagents used in this embodiment and comparative examples are all chemically pure or above.
[0047] Example 1
[0048] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0049] S1. 100 g of cotton cellulose was washed in 500 mL of 25% ethanol by mass, removed and dried, then soaked in 400 mL of hydrochloric acid solution, filtered and washed until the pH of the filtrate was 6.9, and dried to obtain pretreated cotton cellulose;
[0050] S2. 80 g of pretreated cotton cellulose, 80 g of lanthanum nitrate, 160 g of aluminum nitrate, and 160 g of calcium nitrate were mixed and dissolved in 900 mL of water to prepare a first mixed solution; the mixing method was magnetic stirring, the mixing time was 10 min, the dissolution method was ultrasonic dissolution, and the dissolution time was 15 min;
[0051] S3. 300mL 8mmol / L urea was added to the first mixed solution and stirred for 1h to obtain a second mixed solution. The second mixed solution was added to the reactor and heated at 160 ° C for 13h to obtain a precipitate;
[0052] S4. The precipitate was washed with deionized water and anhydrous ethanol 4 times, and dried at 70°C for 13h to obtain a powder;
[0053] S5. The obtained powder is calcined at 600° C. for 5 hours to obtain a material for treating fluoride in wastewater.
[0054] Example 2
[0055] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0056] S1. 100 g of cotton cellulose was washed in 500 mL of 25% ethanol by mass, removed and dried, then soaked in 400 mL of hydrochloric acid solution, filtered and washed until the filtrate pH was 7, and dried to obtain pretreated cotton cellulose;
[0057] S2. 80 g of pretreated cotton cellulose, 80 g of lanthanum nitrate, 240 g of aluminum nitrate, and 160 g of calcium nitrate were mixed and dissolved in 1000 mL of water to prepare a first mixed solution; the mixing method was magnetic stirring, the mixing time was 15 min, the dissolution method was ultrasonic dissolution, and the dissolution time was 20 min;
[0058] S3. 300mL 10mmol / L urea was added to the first mixed solution and stirred for 1.5h to obtain a second mixed solution. The second mixed solution was added to the reactor and heated at 180 ° C for 12h to obtain a precipitate;
[0059] S4. The obtained precipitate was washed 5 times with deionized water and anhydrous ethanol, and dried at 80°C for 12 h to obtain a powder;
[0060] S5. Calcine the obtained powder at 650°C for 4 hours to obtain a material for treating fluoride in wastewater.
[0061] Example 3
[0062] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0063] S1. 100 g of cotton cellulose was washed in 500 mL of 25% ethanol by mass, removed and dried, then soaked in 400 mL of hydrochloric acid solution, filtered and washed until the pH of the filtrate was 7.1, and dried to obtain pretreated cotton cellulose;
[0064] S2. 80 g of pretreated cotton cellulose, 80 g of lanthanum nitrate, 320 g of aluminum nitrate, and 160 g of calcium nitrate were mixed and dissolved in 1200 mL of water to prepare a first mixed solution; the mixing method was magnetic stirring, the mixing time was 20 min, the dissolution method was ultrasonic dissolution, and the dissolution time was 25 min;
[0065] S3. 300mL 10mmol / L urea was added to the first mixed solution and stirred for 2h to obtain a second mixed solution. The second mixed solution was added to the reactor and heated at 200°C for 13h to obtain a precipitate;
[0066] S4. The obtained precipitate was washed 6 times with deionized water and anhydrous ethanol, and dried at 90°C for 11 h to obtain a powder;
[0067] S5. calcining the obtained powder at 700°C for 3 hours to obtain a material for treating fluoride in sewage.
[0068] Example 4
[0069] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0070] S1. 100 g of cotton cellulose was washed in 500 mL of 25% ethanol by mass, removed and dried, then soaked in 400 mL of hydrochloric acid solution, filtered and washed until the filtrate pH was 7, and dried to obtain pretreated cotton cellulose;
[0071] S2. 80 g of pretreated cotton cellulose, 80 g of lanthanum nitrate, 240 g of aluminum sulfate, and 160 g of calcium sulfate were mixed and dissolved in 1000 mL of water to prepare a first mixed solution; the mixing method was magnetic stirring, the mixing time was 15 min, the dissolution method was ultrasonic dissolution, and the dissolution time was 20 min;
[0072] S3. 300mL 10mmol / L urea was added to the first mixed solution and stirred for 1.5h to obtain a second mixed solution. The second mixed solution was added to the reactor and heated at 180 ° C for 12h to obtain a precipitate;
[0073] S4. The obtained precipitate was washed 5 times with deionized water and anhydrous ethanol, and dried at 80°C for 12 h to obtain a powder;
[0074] S5. Calcine the obtained powder at 650°C for 4 hours to obtain a material for treating fluoride in wastewater.
[0075] Example 5
[0076] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0077] S1. 100 g of cotton cellulose was washed in 500 mL of 25% ethanol by mass, removed and dried, then soaked in 400 mL of hydrochloric acid solution, filtered and washed until the filtrate pH was 7, and dried to obtain pretreated cotton cellulose;
[0078] S2. 80 g of pretreated cotton cellulose, 80 g of lanthanum nitrate, 240 g of aluminum chloride, and 160 g of calcium chloride were mixed and dissolved in 1000 mL of water to prepare a first mixed solution; the mixing method was magnetic stirring, the mixing time was 15 min, the dissolution method was ultrasonic dissolution, and the dissolution time was 20 min;
[0079] S3. 300mL 10mmol / L urea was added to the first mixed solution and stirred for 1.5h to obtain a second mixed solution. The second mixed solution was added to the reactor and heated at 180 ° C for 12h to obtain a precipitate;
[0080] S4. The obtained precipitate was washed 5 times with deionized water and anhydrous ethanol, and dried at 80°C for 12 h to obtain a powder;
[0081] S5. Calcine the obtained powder at 650°C for 4 hours to obtain a material for treating fluoride in wastewater.
[0082] Comparative Example 1
[0083] Compared with Example 3, the cotton cellulose was not pretreated in Comparative Example 1.
[0084] A preparation method for treating fluoride in sewage comprises the following steps:
[0085] S1. 80 g of cotton cellulose, 80 g of lanthanum nitrate, 320 g of aluminum nitrate, and 160 g of calcium nitrate are mixed and dissolved in 1200 mL of water to prepare a first mixed solution; the mixing method is magnetic stirring, the mixing time is 20 min, the dissolution method is ultrasonic dissolution, and the dissolution time is 25 min.
[0086] S2. Add 300mL 10mmol / L urea to the first mixed solution in step S1 and continue stirring for 2h to obtain a second mixed solution. The second mixed solution was added to a reactor and heated at 180°C for 13h to obtain a precipitate.
[0087] S3. The obtained precipitate was washed 5 times with deionized water and anhydrous ethanol, and dried at 80°C for 12 h to obtain a powder;
[0088] S4. Calcine the obtained powder at 650°C for 4 hours to obtain a material for treating fluoride in sewage.
[0089] Comparative Example 2
[0090] In this comparative example 2, cotton cellulose, lanthanum nitrate, aluminum nitrate and calcium nitrate are directly mixed.
[0091] This embodiment is a preparation of a material for treating fluoride in sewage, comprising the following steps:
[0092] Mix together 8 mg of cotton cellulose, 8 mg of lanthanum nitrate, 32 mg of aluminum nitrate, and 16 mg of calcium nitrate.
[0093] Comparative Example 3
[0094] This comparative example 3 adopts the existing method for preparing defluorination materials, specifically a method for preparing a deep defluorination material in patent CN117534169A, including the following steps:
[0095] S1. According to the molar ratio of sodium carbonate to sodium hydroxide being 1:1, 10.60 g of sodium carbonate and 4 g of sodium hydroxide were dispersed in 200 mL of water to obtain a mixed solution (concentration of 1 mol / L); 20 g of walnut shell powder (particle size of 0.5 μm) was dispersed in the mixed solution to obtain a carbon template solution;
[0096] S2. Under room temperature and stirring conditions at 400 rpm, 200 mL of 0.5 mol / L lanthanum isopropoxide aqueous dispersion was dropwise added to the carbon template solution for precipitation reaction for 30 min to obtain an organic lanthanum basic carbonate material loaded on the emulsion carbon template;
[0097] S3. The organic lanthanum carbonate material loaded on the emulsion carbon template was placed in a 5MPa high pressure reactor, and the polymerization reaction was carried out at 160°C for 12h, and the reaction was naturally cooled after completion;
[0098] S4. The cooled product was separated by suction filtration, washed three times with clean water and ethanol alternately, dried at 60°C, and finally ground into fine powder with a particle size of 400 mesh.
[0099] The materials for treating fluoride in sewage prepared in Examples 1-5 and Comparative Examples 1-3 were used to remove fluoride in aqueous solutions containing fluoride at different contents.
[0100] Verification Example 1:
[0101] Eight portions of 120 mL of a fluorine-containing aqueous solution with a fluorine concentration of 50 mg / L were prepared, the pH was adjusted to 7, 20 mg of the material for treating fluoride in sewage prepared in Examples 1-5 and Comparative Examples 1-3 were added respectively, and the reaction was stirred at room temperature for 1 h, 2 h, 3 h, 4 h, 5 h, and 10 h respectively; the fluorine concentration of the liquid was tested, and the fluorine concentration test was shown in Table 1.
[0102] Table 1 Treatment effect of different defluorination materials on 50 mg / L fluoride-containing aqueous solution
[0103]
[0104] As can be seen from Table 1, the material for treating fluoride in sewage prepared by the present invention can reduce the fluoride ion concentration to below 1 mg / L after treating fluoride-containing sewage with an initial fluoride concentration of 50 mg / L for 2 hours. For fluoride-containing sewage with a fluoride content of less than 50 mg / L, the fluoride ion concentration can also be reduced to below the prescribed limit after being treated for 2 hours using the material for treating fluoride in sewage of Examples 1-5 of the present invention. The specific components used for the soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt have little effect on the test results.
[0105] Comparing Examples 1-5 with Comparative Example 3, it can be seen that although cotton cellulose, lanthanum nitrate, aluminum nitrate, and calcium nitrate have certain defluorination capabilities, the effect is limited and cannot meet the standard defluorination requirements. Comparing Examples 1-5 with Comparative Example 1, it can be seen that if the biological template is not pretreated in the original step S1, the processing capacity of fluoride ions is stronger than that of Comparative Example 3, but the improvement is limited and still does not achieve the ideal defluorination effect. This shows that the pretreatment of the biological template and the co-precipitation of soluble lanthanum salts, aluminum salts, calcium salts and biological templates and the calcination process are all indispensable steps to improve the adsorption capacity of raw materials.
[0106] Comparing Comparative Example 2 with Comparative Example 3, their defluorination capabilities are significantly lower than those of Examples 1-5 and Comparative Example 1. In Comparative Example 3, the experimental results in the public text of CN117534169A are better, but it is applied in "100 mL of fluorine-containing aqueous solution with a fluorine concentration of 20 mg / L", and the amount of carbon template-loaded lanthanum carbonate defluorination material is 100 mg, and the test time is 30 min, and no test experiment for higher concentration fluorine-containing wastewater is given. The amount of fluoride treatment material in sewage in Examples 1-5 is 20 mg, indicating that the preparation method of the fluoride treatment material in sewage prepared by the present invention can greatly improve the adsorption rate and defluorination efficiency of the raw materials, and the prepared material can achieve the adsorption and removal of higher concentration fluoride ions at a lower dosage.
[0107] Verification Example 2:
[0108] Eight portions of 120 mL of a fluorine-containing aqueous solution with a fluorine concentration of 20 mg / L were prepared, the pH was adjusted to 7, and 20 mg of the fluoride treatment material for sewage prepared in Examples 1-5 and Comparative Examples 1-3 were added respectively, and the fluorine concentration of the liquid was tested for 5 min, 10 min, 15 min, 20 min, and 30 min at room temperature. The fluorine concentration test is shown in Table 2.
[0109] Table 2 Treatment effect of different defluorination materials on 20 mg / L fluoride-containing aqueous solution
[0110]
[0111] As can be seen from Table 2, the material for treating fluoride in sewage prepared by the present invention can reduce the fluoride ion concentration to below 1 mg / L after treating fluoride-containing sewage with an initial fluoride concentration of 20 mg / L for 15 minutes. For fluoride-containing sewage with a fluoride content of less than 20 mg / L, the fluoride ion concentration can also be reduced to below the prescribed limit after being treated with the material for treating fluoride in sewage of Examples 1-5 of the present invention for 15 minutes. For Comparative Example 3, the fluoride content can be reduced to below the 1 mg / L standard after 20 minutes of treatment, indicating that the present invention removes fluoride faster than the comparative example.
[0112] Comparative Examples 1 and 2 cannot achieve the desired defluorination effect.
[0113] Verification Example 3:
[0114] Eight portions of 120 mL of a fluorine-containing aqueous solution with a fluorine concentration of 5 mg / L were prepared, the pH was adjusted to 7, 20 mg of the material for treating fluoride in sewage prepared in Examples 1-5 and Comparative Examples 1-3 were added respectively, and the fluorine concentration of the liquid was tested at room temperature for 1 min, 3 min, 5 min, and 10 min. The fluorine concentration test is shown in Table 3.
[0115] Table 3 Treatment effect of different defluorination materials on 5 mg / L fluoride-containing aqueous solution
[0116]
[0117] As shown in Table 3, the material for treating fluoride in sewage prepared by the present invention can reduce the fluoride ion concentration to below 1 mg / L after treating fluoride-containing sewage with an initial fluoride concentration of 5 m / L for 3 minutes. For Comparative Example 3, although the fluoride content can be reduced to below the 1 mg / L standard after treating for 3 minutes, its residual fluorine content is greater than the test results of Examples 1-5, indicating that the defluoridation material of the present invention has more abundant fluoride ion adsorption sites than those.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A material for treating fluoride in sewage, characterized in that: The material for treating fluoride in sewage is calcium-modified aluminum-lanthanum mixed metal oxide, and its raw materials include biological template, soluble lanthanum salt, soluble aluminum salt, soluble calcium salt and urea; The biological template is cotton cellulose, and the length of the cotton cellulose fiber is 0.5 to 3 cm; The method for preparing the material for treating fluoride in sewage comprises the following steps: S1, washing the bio-template with alcohol, taking it out and drying it, then soaking it in a hydrochloric acid solution, filtering and washing it until the pH of the filtrate is 6.9-7.1, and drying it to obtain a pretreated bio-template; S2, mixing the pretreated bio-template, soluble lanthanum salt, soluble aluminum salt, and soluble calcium salt in water, and ultrasonically dissolving for 15 to 25 minutes to obtain a first mixed solution; the weight ratio of the bio-template, lanthanum ions, aluminum ions, and calcium ions is 10:3:(1.4 to 2.8):4; the soluble lanthanum salt is one of lanthanum nitrate, lanthanum chloride, and lanthanum acetate; the soluble aluminum salt is one of aluminum chloride, aluminum sulfate, and aluminum nitrate; the soluble calcium salt is one of calcium chloride, calcium sulfate, and calcium nitrate; S3, adding urea to the first mixed solution and stirring to obtain a second mixed solution, adding the second mixed solution to a reactor and heating to obtain a hydroxide precipitate; S4, washing the obtained hydroxide precipitate with deionized water and anhydrous ethanol for more than 3 times, and then drying at 70-90° C. for more than 11 hours to obtain a powder; S5. calcining the obtained powder at a temperature of 600-700° C. for 3-5 hours to obtain calcium-modified aluminum-lanthanum mixed metal oxide, which is a material for treating fluoride in sewage.
2. The material for treating fluoride in sewage according to claim 1, characterized in that: The biological template is in the form of floccules or fleece.
3. The material for treating fluoride in sewage according to claim 1, characterized in that: In step S1, the organic solvent used for alcohol washing is isopropanol or 25% ethanol; In step S2, the first mixed solution is mixed by magnetic stirring, the magnetic stirring speed is 500-100 rpm, and the mixing time is 10-20 min; In step S3, the molar concentration of urea in the second mixed solution is 8-12 mmol / L, and the heating temperature of the second mixed solution is 160-200°C.
4. An application of the material for treating fluoride in sewage as claimed in claim 1, characterized in that: The invention is applied to remove fluoride ions from fluoride-containing wastewater; based on the volume of the fluoride-containing wastewater, the dosage of the fluoride treatment material in the wastewater is 1 to 1.5 g / L.
5. The use of a material for treating fluoride in sewage according to claim 4, characterized in that: For sewage with a fluoride content of ≤5 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment materials in the sewage shall not be less than 3 minutes; For sewage with a fluoride content greater than 5 mg / L and not more than 20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment materials in the sewage shall not be less than 15 minutes; For sewage with a fluoride content ≥ 20 mg / L, the stirring and mixing time of the fluoride-containing sewage and the fluoride treatment materials in the sewage shall not be less than 2 hours.
6. The use of a material for treating fluoride in sewage according to claim 5, characterized in that: The material for treating fluoride in sewage is regenerated every 5 to 7 days. The regeneration method is as follows: solid-liquid separation is performed on the fluoride-containing sewage to which calcium-modified aluminum-lanthanum mixed metal oxide is added, and the solid is soaked in a 0.4 to 0.6 mol / L sodium hydroxide solution for 22 to 26 hours, followed by centrifugation and drying to obtain the regenerated material for treating fluoride in sewage.
Citation Information
Patent Citations
Preparation method of calcium-aluminum-lanthanum-based compound fluorine-removing material
CN102389769A